Mind-Craft: Exploring the Effect of Digital Visual Experience on Changes to Orientation Sensitivity in Visual Contour Perception. (October 2020) - Hipp, D.; Olsen, S.; Gerhardstein, P.
Visual perception depends fundamentally on statistical regularities in the environment to make sense of the world. One such regularity is the orientation anisotropy typical of natural scenes; most natural scenes contain slightly more canonical (horizontal and vertical) information than oblique information. This property is likely a primary cause of the oblique effect in which subjects experience greater perceptual fluency with horizontally and vertically oriented content than oblique. Recent changes in the visual environment, including the "carpentered" content in urban scenes and the framed, caricatured content in digital screen media presentations, may have altered the typical (natural) level of orientation anisotropy. The current work evaluated whether digital visual experience, or visual experience with framed digital content, has the potential to alter the magnitude of the oblique effect in visual perception. Experiment 1 successfully established a novel eye-tracking method capable of indexing the visual oblique effect quickly and reliably and demonstrated the oblique effect. Experiment 2 used this method and found that one session of exposure to a specific video game altered visual orientation perception. Taken together, these results indicate that exposure to the realistic, but caricatured scene statistics of digital screen media, can alter visual contour perception in one session.